Type material housed in the Carcinological Collection of the Museo de La Plata, Argentina - Diaz, Analía R.; Álvarez, Victor Hugo Merlo; Damborenea, Cristina (Zootaxa, 2017)
The Carcinological Collection of División Zoología Invertebrados, Museo de La Plata (FCNyM-UNLP) includes of 110 type lots of 42 species. A list of types of the crustacean orders Anostraca (8 species), Diplostraca (5 species), Arguloida (3 species), Cyclopoida (1 species), Poecilostomatoida (8 species), Siphonostomatoida (2 species), Podocopida (4 species), Amphipoda (2 species), Isopoda (2 species), Mysida (2 species) and Decapoda (5 species) is presented. Species names are listed in systematical order, including type locality, collection number, current taxonomic status and original bibliographic reference. For parasite and commensal species, type host and site of infection are also provided.